2013
DOI: 10.1002/psc.2515
|View full text |Cite
|
Sign up to set email alerts
|

Stabilisation of a short α‐helical VIP fragment by side chain to side chain cyclisation: a comparison of common cyclisation motifs by circular dichroism

Abstract: A model octapeptide segment derived from vasoactive intestinal peptide (VIP) was utilised to investigate the effect of several conventional cyclisation methods on the α-helical conformation in short peptide fragments. Three of the classical macrocyclisation techniques (i.e. lactamisation, ring-closing metathesis and Huisgen cycloaddition) were applied, and the conformations of the resulting cyclic peptides, as well as their linear precursors, were compared by CD analysis. The visibly higher folding propensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…At the concentrations of 50 and 75 μM, the CD spectrum signature appears to conform to a mixed random/helix/β‐sheet intermediary state . Studies concerning parts of the CspB protein have established that helix and β‐sheet secondary structures, as well as random coil state, contribute to the formation of amyloid fibers .…”
Section: Resultsmentioning
confidence: 99%
“…At the concentrations of 50 and 75 μM, the CD spectrum signature appears to conform to a mixed random/helix/β‐sheet intermediary state . Studies concerning parts of the CspB protein have established that helix and β‐sheet secondary structures, as well as random coil state, contribute to the formation of amyloid fibers .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the dipolarity of the triazole compares well to the amide's (Scheme 32, right). [262][263][264] The 1,2,3-triazole has been used to stabilize secondary structures or other motifs, including α-helices 265,266 3 10 -helices, 262,267 β-hairpins, 268 and disulfides. 21,269 The reaction has been used extensively for, among others, bioconjugation and materials science, with comprehensive reviews available.…”
Section: C-c Triple Bond Formation: Ringclosing Alkyne Metathesismentioning
confidence: 99%
“…264 When a short spacer on the C-terminus is desired for headto-tail cyclization, it is possible to introduce a C-terminal propargylamine by using a silyl-based alkyne modifying (SAM)-resin. 272,273 CuAAC does not require protecting groups and can be performed on-resin 267,271,[274][275][276][277][278] as well as in solution, 262,[265][266][267][268][269][279][280][281][282][283][284][285][286][287][288][289][290][291][292][293][294][295] which is more common and proceeds under mild conditions. Cu salts most frequently used are CuSO 4 with sodium ascorbate, or Cu I salts such as CuI and…”
Section: C-c Triple Bond Formation: Ringclosing Alkyne Metathesismentioning
confidence: 99%
“…The α-helix, one of the most abundant and important secondary structures in proteins, has been a primary target in the fi eld of peptide conformation stabilization. [1][2][3][4][5][6][7] Studies have shown that a peptide α-helix can be stabilized by conformational nucleation, [8][9][10][11] structural rigidifi cation, [ 12 ] and molecular self-assembly. [ 13,14 ] In…”
Section: Introductionmentioning
confidence: 99%
“…Because of the utility of peptides in modulating protein‐mediated interactions, many studies have been performed on the stabilization peptide conformations. The α‐helix, one of the most abundant and important secondary structures in proteins, has been a primary target in the field of peptide conformation stabilization …”
Section: Introductionmentioning
confidence: 99%